Time-based Magnetic Flux Leakage Assessment of SAE1045 Steel for Biaxial Fatigue Failure - N. Sahadan, S.; Abdullah, S.; Arifin, A. (International Journal of Engineering and Technology, 2018)
In this study it is aim to investigate behaviour of magnetic metal memory, MMM signal the stress concentration zone of ferromagnetic material using magnetic flux leakage under cyclic axial-torsional loading and later estimating the life of the specimens. Specimen in this study made from SAE 1045 steel prepared according to ASTM E466-01 for cyclic testing. In this study, it is proposed to take the signal using time based method during experiment. Load in axial and torsional direction is given and two types of sensors attach to the specimen; the strain gauge and the MMM sensor. Data is collected in time-based for both sensors. Trend of data from both sensors were then tabulation. It shows that both sensors has similar trend along the experiment when each signals shows important event during experiment such as at loading and at fracture. After that the estimated life from the MMM sensor, the Tlife was then compared to numbers of cycle to failure from the experiment. It shows that this proposed method has the ability to estimated fatigue life with better accuracy when the specimens have higher number of cycle.Â Â Â